Managing the Quantitative and the Qualitative : Innovating on the Dynamics of Performance Measurements, Professional Attitudes and Quality of Organizational Social Work Services in Sunshine Social Service Centre, Dezhou, China - Hou Ming; Hanif Abdurahman Siswanto; Mohammad Reevany Bustami; Zaenal Abidin; Liu Wankun (Journal of Economics, Business, and Accountancy Ventura, 2025)
This article is based on a research with a three-prong objectives. The first is to examine the connection between the attitudes of the social workers and their work execution quantified using PMT. The second is to investigate the connection between the performance measurement with the quality of the social services. The third is to analyze the link between social workers’ attitudes and the quality of social services. The essence is to explain the interconnection between the quantifiable measurements and the more subjective or qualitative attitudes vis-à-vis the quality of the social services rendered. The methodology employed is sequential explanatory research, whereby the quantitative data of 14 social workers from Sunshine Social Work Service Centre in Dezhou City, China will be explained by the qualitative deliberations. The results show that the first hypothesis that social workers oppose performance evaluation (PMT) is not supported while performance evaluation results directly impact social service project quality though it is not as significant as the attitude of social workers to achieve quality of social services. This suggests that the scientific rationality of current PMTs still requires improvement while positive attitudes of social workers towards performance evaluation contribute to achieving good outcomes in social service projects.